KAJIAN KEBIJAKAN DAN PENGEMBANGAN SEKTOR INFORMAL KOTA PEMATANGSIANTAR - Fauzi . (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
Today, the presence of the urban informal sector is considered one of the emerging economic sectors as a result of the city's high employment growth situation. Those who enter this small-scale business, initially aimed at finding job opportunities and creating income. Identify the distribution of informal sector of Pematangsiantar City, using data from plotting surveys using GPS (Global Positioning System). The distribution of business actors / informal sector activities is identified based on the number of samples taken in conjunction with the dissemination of questionnaires. The number of samples itself is determined using sampling method. The calculation itself is done by means of the number of respondents who choose one of the variables divided by the total number of respondents, namely 50 (fifty) correspondents. Weighting on internal factors of importance is based on the large influence of strategic factors on its strategic position (Freddy Rangkuti, 2001 : 22-24). The number of weights on each internal factor must amount to = 1 (one) : Total Internal Score → Total Strength Weight + Total Weight Weakness = 1. While the value of weight according to Freddy Rangkuti (2001: 22-24) and Training Spama (2000: 13-14) based on the following provisions: "Scale 1.0 (very important) up to 0.0 (not important)". The average weight value depends on the number of strategic factors (5-10 strategic factors) used After doing the analysis, it can be known that in strengths variables that have the highest sub total is creativity with a value of 0.640. And for weaknesses that have the highest sub total is the source of capital with a value of 0.270. Conclusions based on the results of identification and analysis of the Study of Development and Informal Sector Of Pematangsiantar City, then some conclusions that can be drawn as follows, the Internal Development factor of informal sector of the City of Pematangsiantar consists of several factors of strengths and weaknesses. Variables of the strength of the informal sector of Pematangsiantar City are: motivation, creativity, many kinds / types of business, small capital, and work experience. The variables of the weakness of the informal sector of pematangsiantar city are: level of education, lack of permits, availability of raw materials, facilities and infrastructure, as well as sources of capital